TINDAKAN SOSIAL DALAM NOVEL KITA PERGI HARI INI KARYA ZIGGY ZEZSYAZEOVIENNAZABRIZKIE BERDASARKAN PERSPEKTIF MAX WEBER - Hidayah, Hildan Nurul (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
In the sociology of literature, social action is interpreted as a form of individual behavior to achieve a goal, without social action, social relations will be passive. This study aims to identify and describe the forms of social action in the characters in the novel We Go Today by Ziggy Zezsyazeoviennazabrizkie. This study uses a qualitative method with descriptive analysis, the primary data sources are dialogues and author's narration in the novel We Go Today. Collecting data using the read and sign method, then data analysis through the transcription stage and then data reduction to produce some data that is relevant to Max Weber's theory. The results of this study found 12 forms of social action. 3 in the form of instrumental rational actions, 5 traditional non-rational actions, and 4 affective rational actions.